2003
DOI: 10.1080/0267152032000107301
|View full text |Cite
|
Sign up to set email alerts
|

How do primary school teachers define and implement ‘interactive teaching’ in the National Literacy Strategy in England?

Abstract: This paper reports the methods and findings of the Study of Primary Interactive Teaching (SPRINT) project carried out in English primary schools, which set out to determine teachers' understanding and use of 'interactive teaching' as a characteristic of 'successful teaching' in the National Literacy Strategy (NLS). Thirty teachers of children aged five to 11 years became either 'focus' teachers or 'comparison ' teachers and were videoed twice over a six to eight month period doing 'interactive teaching' during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 8 publications
2
38
0
4
Order By: Relevance
“…This poses a challenge for teachers (see, e.g. Hargreaves et al 2010). Teachers should create the opportunity for all students to express their points of view, leaving more control to the students.…”
Section: Guiding Classroom Discussion For Democratic Citizenship Edumentioning
confidence: 99%
“…This poses a challenge for teachers (see, e.g. Hargreaves et al 2010). Teachers should create the opportunity for all students to express their points of view, leaving more control to the students.…”
Section: Guiding Classroom Discussion For Democratic Citizenship Edumentioning
confidence: 99%
“…Each musical activity was filmed to provide the stimulus for subsequent semi-structured group interviews with the children (n=5/6 in each group) using video-stimulated reflective dialogue (VSRD). VSRD is an established research tool which has been used in research with both teachers (for example Hargreaves et al, 2003;Morgan, 2007;Powell, 2005;Pratt, 2006;Tanner, Jones, & Lewis, 2010) and pupils (Salisbury, Ellis, Beauchamp, & Haughton, 2011;Tanner & Jones, 2007) as it is effective in initiating dialogue between participants and interviewers. Indeed, the use of dialogue is central to the process of VSRD, which distinguishes it from video stimulated recall or video stimulated reflection.…”
Section: Methodsmentioning
confidence: 99%
“…This means that reflection is based on three fragments that show positive (examples of) teacher behavior and one fragment that shows (an example of) teacher behavior that might be improved in the future. Several scholars (Fukkink et al 2011;Hargreaves et al 2003;Kennedy et al 2011) have demonstrated that employing video feedback methods has positive effects on teachers' use of stimulating behavior, sensitive responsivity, and verbal stimulation.…”
Section: Video Feedback Coachingmentioning
confidence: 99%